State and private school in Spain: creeping segregation - Fernández Enguita, Mariano (Profesorado, Revista de Currículum y Formación del Profesorado, 2008)
The global distribution of students between state and private school has scarcely changed along the recent period (2(3 and 1/3 of the age group school populations, respectively), but this should not hide three deeper processes. First, access to private schools (state granted or privately funded) is growing in middle and big cities and among the higher social classes, better equipped in economic and cultural terms. Second, inside the private school sector there is also a move from state granted schools (which are free for parents) to privately funded (with parents’ fees) ones. Last bur not least, the apparent stability of stocks hides mayor changes in flows: sate schools are losing pupils among middle and higher social strata while growing among more disadvantaged ones, so being obliged to assume the bulk of the effort aimed to the integration of most needy pupils.